Rights and knowledge-based approach to aging and disability: an overview of issues and approaches - Olga Krassioukova-Enns; Laurie Ringaert (Social Welfare: Interdisciplinary Approach, 2012)
This analysis paper is part of a larger project led by the Canadian Centre on Disability Studies (CCDS) and funded by Human Resources and Social Development Canada (HRSDC), called “From Research and Knowledge to Better Practice: Building Strategies and Partnerships for Livable Communities That are Inclusive of Seniors with Disabilities” (2008-09). The central purpose of the larger project was to develop and test a model of livable and inclusive communities that includes the needs, preferences, and circumstances of seniors with disabilities. A participatory method was used to accomplish this goal by identifying the key principles and elements of what makes communities livable and inclusive for seniors with disabilities and to develop and test a Livable and Inclusive Community Evaluation Tool and process to measure the extent to which the community meets their needs. In addition, a Livable and Inclusive Community Planning Tool was developed and introduced to several pilot communities across Canada. This paper provides an overview of issues, needs and approaches to disability and aging and is the beginning of the subsequent series of papers. In this discussion the terms “seniors” and “older adults” are used interchangeably refl ecting the fl exible use of the terms in the North American context.